Title: Experiences of studying Trauma in a Person Centred Learning Group - Humberstone, Kathy (2017)
This research explores the experiences of a person centred learning group engaged in a Masters qualification in Trauma Studies. As both researcher and group participant I have been keen to discover if my peers have experienced a similar transformational learning experience to myself. Psychological trauma is normally studied in the United Kingdom in the context of skills and techniques designed to treat symptoms of posttraumatic stress. Trauma Studies as studied within a person centred group is unique and therefore worthy of examination. Within a qualitative methodological design non-directional interviews were conducted with 7 participants and a thematic analysis was used following the principles of interpretative phenomenological analysis. Three superordinate themes emerged from the data: intellectual understanding, the lived experience and inner experiencing of person centred education. Subordinate themes related to a difficulty in understanding the learning concept, the importance of the group relationship, and personal and professional changes that participants reported. The results raise the profile of person centred education, and have important implications for the way trauma is studied in the United Kingdom.